PARTISIPASI MASYARAKAT DALAM REHABILITASI LAHAN DAN KONSERVASI TANAH (RLKT) DI SUB DAS KEDUANG, KABUPATEN WONOGIRI, JAWA TENGAH - Nur Ainun Jariyah (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Keduang Sub Watershed is one of major contributors of sedimentation in Gajah Mungkur reservoir. Since soil conservation projects usually involve a number of small-scale farmers, the success of the projects is likely determined by farmers' participation in all phases of the projects. This study aimed to examine the community participation in land rehabilitation and soil conservation in Ngadipiro village. This research was conducted in Dungwot sub watershed, Ngadipiro village, Nguntoronadi district, Wonogiri regency in Central Java. Data was collected by survei method, using face to face interviews and focused group discussions, which involved the owners of farmlands designated as demonstration plots, community leaders, and farmer group leaders. Data analysis was done by descriptive statistics. The results are as follows: the level of education affects the absorption of information and participation. High pressure on land, as indicated by livelihoods dominated by agriculture and land use dominated by agricultural land. Participation in the Ngadipiro village can be categorised by participation formaterial incentives. In the ladder of participation,Ngadipiro village falls into the consultation stage